Atresia congénita del esófago. - Ugarte Suárez, José Carlos; Medina García, Noel; Banasco Domínguez, Jorge (Revista Cubana de Pediatría, 2023)
Establecer experiencia en el manejo radiológico de los casos, y seguir su evolución.